Pengelolaan Cache pada Aplikasi Pencatatan Penjualan Menggunakan Fuzzy Page Replacement Algorithm - Julastri, Bregsi Atingsari; Sari, Anggraini Puspita; Prami Swari, Made Hanindia (JURNAL INFORMATIKA DAN KOMPUTER, 2024)
The challenges faced in website development are becoming increasingly diverse, particularly in delivering a responsive website that aligns with user preferences. Progressive Web App (PWA) is an advanced web technology that combines the advantages of mobile applications with the ease of access provided by browsers. With features such as offline access and responsiveness across various devices through the utilization of web caching, PWA can offer a better and more interactive user experience. This study aims to develop a sales recording application based on PWA, optimized using an algorithm with a fuzzy approach, namely the Fuzzy Page Replacement Algorithm (FPRA) in cache management. FPRA is applied to enhance cache efficiency through the clustering of pages based on recency, access frequency, and page reference levels using the Fuzzy C-Means algorithm. The research was conducted with a case study on the sales recording application for a fried chicken business, employing the Rapid Application Development (RAD) method for the design and construction of the application. The results indicate that FPRA successfully reduced page load time significantly, achieving up to 37% faster performance based on the average results of five tested scenarios. The implementation of FPRA in the service worker also increased the average performance score of the application by 15 points, from 56 to 71, as evaluated using the Lighthouse testing tool. Thus, the utilization of caching and the application of FPRA in cache management have been proven to enhance application performance.